Enrichment of Maize Grains with Zinc through Agronomic Biofortification - R.M. Karmakar and D. Tamuly, G.G. Kandali*, N. Yadav (Journal of the Indian Society of Soil Science, 2021)
A field experiment was conducted at instructional-cum-research farm of Assam Agricultural University, Jorhat, Assam to enrich zinc (Zn) in grains of a hybrid maize variety (PAC 740) through soil application of Zn with six levels of ZnSO4.7H2O viz. 0, 20, 40, 60, 80 and 100 kg ha-1 with and without foliar spray of 0.5% ZnSO4.7H2O at tasseling stage. Highest grain yield (7.83 t ha-1) was recorded with 60 kg ZnSO4.7H2O (soil) + 0.5% foliar spray. Significant increase in grain yield over control was observed at 40 kg ZnSO4.7H2O and above. Foliar application of Zn though improved yield, but statistically had no effect on yield, plant height and number of grains per cob between graded doses of Zn with and without foliar application. However, grain Zn concentration and uptake were more effectively increased by Zn fertilization, especially with soil and foliar applications. Significantly highest grain Zn concentration (46.9 mg kg-1) and uptake of Zn (358.2 g ha-1) was observed with 100 kg ZnSO4.7H2O ha-1 (soil)+0.5% foliar application over control. Nitrogen and potassium concentration and uptake by grains increased with the increasing level of Zn but phosphorus concentration and uptake decreased. Agronomic efficiency and apparent recovery efficiency was found highest in the treatment with 60 kg ZnSO4.7H2O ha-1 (soil)+0.5% foliar application. Soluble protein increased significantly over control with 40 kg ZnSO4.7H2O ha-1 (7.41%) and above. Although, crude protein and starch content increased with the increase in Zn concentration, the effect was not significant with increasing dose of ZnSO4.7H2O.